Measurement of boosted Higgs bosons produced via vector boson fusion or gluon fusion in the H → b b ¯ $$ b\overline{b} $$ decay mode using LHC proton-proton collision data at s $$ \sqrt{s} $$ = 13 TeV - The CMS collaboration; A. Hayrapetyan; A. Tumasyan; W. Adam; J. W. Andrejkovic; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; P. S. Hussain; M. Jeitler; N. Krammer; et al. (Journal of High Energy Physics, 2024)
Abstract A measurement is performed of Higgs bosons produced with high transverse momentum (p T) via vector boson or gluon fusion in proton-proton collisions. The result is based on a data set with a center-of-mass energy of 13 TeV collected in 2016–2018 with the CMS detector at the LHC and corresponds to an integrated luminosity of 138 fb −1. The decay of a high-p T Higgs boson to a boosted bottom quark-antiquark pair is selected using large-radius jets and employing jet substructure and heavy-flavor taggers based on machine learning techniques. Independent regions targeting the vector boson and gluon fusion mechanisms are defined based on the topology of two quark-initiated jets with large pseudorapidity separation. The signal strengths for both processes are extracted simultaneously by performing a maximum likelihood fit to data in the large-radius jet mass distribution. The observed signal strengths relative to the standard model expectation are 4.9 − 1.6 + 1.9 $$ {4.9}_{-1.6}^{+1.9} $$ and 1.6 − 1.5 + 1.7 $$ {1.6}_{-1.5}^{+1.7} $$ for the vector boson and gluon fusion mechanisms, respectively. A differential cross section measurement is also reported in the simplified template cross section framework.